Glucose metabolism in rats submitted to skeletal muscle denervation - Nunes, Wilton Marlindo Santana [UNESP]; Mello, Maria Alice Rostom de [UNESP] (Brazilian Archives of Biology and Technology, 2005)
O estudo analisou os efeitos locais e sistêmicos da imobilização por desnervação do músculo esquelético sobre o metabolismo glicidico. Ratos foram submetidos à secção do nervo ciático da pata direita. Observou-se redução da captação de glicose pelo músculo sóleo isolado da pata desnervada após 3 e 7 mas não após 28 dias em relação a animais controle. Não houve diferença após 3 e 7 dias na captação de glicose pelo músculo sóleo da pata contralateral intacta em relação ao controle. Houve aumento da captação de glicose nesta mesma pata 28 dias após a desnervação. A taxa de remoção da glicose em resposta à insulina exógena após 28 dias de desnervação foi significantemente superior à do controle e àquelas observadas após 3 e 7 dias da desnervação. Esses resultados sugerem que a imobilização por desnervação interfere não só no metabolismo da glicose no músculo esquelético envolvido como também em outros tecidos.

This study analyzed the local and systemic effects of immobilization by denervation of the skeletal muscle on glucose metabolism. The rats were submitted to section of the right paw sciatic nerve. A reduction was observed in glucose uptake by the isolated soleus muscle of the denervated paw after 3 and 7 days, but not after 28 days in relation to the control animals. There was no difference after 3 and 7 days in glucose uptake by the soleus muscle of the opposite intact paw in relation to the control. There was increased glucose uptake in the same paw 28 days after denervation. The rate of glucose removal in response to exogenous insulin after 28 days of denervation was significantly higher than in control animals and those observed after 3 and 7 days of denervation. These results suggest that immobilization by denervation interfered not only in glucose metabolism in the skeletal muscle involved but also in other tissues.
Keywords: Denervation; Glucose metabolism; Skeletal muscle